ANALISIS YURIDIS ATAS HASIL LELANG YANG TIDAK MENCUKUPI NILAI KREDIT (STUDI PADA PT. BANK RAKYAT INDONESIA, TBK CABANG ISKANDAR MUDA & KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG) - RIA JULIANA SIREGAR (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Muhammad Yamin3. Sutiarnoto Law has strategic and dominant position in society, state, and nation. In a constitutional state, the government guarantees law enforcement and its goal. The same is true to social life in which humans need financial aid for their daily needs or for their business capital. It can be obtained from the banks or from other financial institutions; it is called credit.Keywords: Proceeds of Auction, KPKNL, Credit Value